1967
DOI: 10.1128/jb.93.4.1281-1288.1967
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Uptake in an Obligately Marine Fungus II. Role of Culture Conditions, Energy Sources, and Inhibitors

Abstract: Phosphate uptake in the obligately marine fungus, Thraustochytrium roseum, is maximal at pH 7.5 to 7.8, is dependent on temperature, and varies with phosphate concentration. Pyruvate and succinate stimulate phosphate uptake, although they do not increase respiration. The uncoupling agents, 2,4-dinitrophenol and dicoumerol, inhibit phosphate uptake but stimulate oxygen consumption only in the presence of NaCl. Oligomycin inhibits both processes. Among the inhibitors of protein synthesis, chloramphenicol reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…There are conflicting reports regarding the number and the kinetic properties of the uptake systems of the yeast Saccharomyces cerevisiae (2,3,8,15). The differences may be due, in part, to differences in the culture conditions before assay, since, in studies with other fungi, phosphate uptake ability has been found to be increased after growth in low-phosphate media (4,27,28). The most extensive study of phosphate uptake by a filamentous fungus has been carried out recently with Neurospora crassa (18)(19)(20).…”
mentioning
confidence: 99%
“…There are conflicting reports regarding the number and the kinetic properties of the uptake systems of the yeast Saccharomyces cerevisiae (2,3,8,15). The differences may be due, in part, to differences in the culture conditions before assay, since, in studies with other fungi, phosphate uptake ability has been found to be increased after growth in low-phosphate media (4,27,28). The most extensive study of phosphate uptake by a filamentous fungus has been carried out recently with Neurospora crassa (18)(19)(20).…”
mentioning
confidence: 99%
“…In contrast to the mycelial fungi discussed above, there is evidence that zoosporic genera in the Thraustochytriales require sodium chloride for growth. Siegenthaler et al [ 77 , 78 ] suggested that phosphate uptake in Thraustochytrium roseum required sodium chloride. Also, they demonstrated that the presence of the amino acid proline in their cells, as well as high levels of inorganic ions which contribute to the solute potential of the cells.…”
Section: Physiological Response To Salinitymentioning
confidence: 99%